0100 Exploring simulation fellowship: A survey of current practice and our local experience in developing a fellowship network. (2nd November 2015) - Simpson, Thomas; Roycroft, Jennifer; Reedy, Gabriel
Abstract : Background: The evolution of simulation training in medical education has been accompanied by the development of specialised programmes for staff to develop experience and expertise in simulation, often referred to as Fellowships. There are no established guidelines for what such a fellowship should consist of, although a BMJ careers document from 2010 outlines likely roles and responsibilities. Anecdotal evidence suggests that the quality and content of fellowships vary across centres. A survey of programmes in the US showed high fill-rates for fellowship programmes but identified significant differences in pre-requisites. We wished to assess the experience of current fellows, whilst also discussing the genesis of a network aimed at professional development of fellows within our collaborative network, the South London Simulation Network. Methodology: A survey was designed with input from fellows and senior faculty within one centre. There exists no robust database of simulation centres or of simulation fellows employed nationwide. Internet searches were employed to identify centres and a standard e-mail link to an online survey sent, requesting forwarding to any known Fellows. Numerous examples of propagation through personal contact occurred causing a snowball-effect in responses. Concurrently a local network of fellows has commenced with the aim of fostering personal and career development amongst fellows at different but connected centres. Results: The survey is ongoing with 40 responses at the time or writing from a nationwide spread of centres. The local network will have met on two occasions by the time of conference. We will discuss the comprehensive results of our work at conference. Potential impact: This presentation will inform the development of local and national policies regarding Simulation Fellowships and should assist in the development of minimum standards for fellows, fellowships and their employing departments. References: Kotal ER, et al . A survey of simulation fellow programs. J Emerg Med. 2015;48(3):351–5 Mercer S, Jones ND, Gupta A. A clinical fellowship in simulation in Healthcare . 2010. http://careers.bmj.com/careers/advice/view-article.html?id=20000744